Candidatus Desulfofervidus auxilii, a hydrogenotrophic sulfate‐reducing bacterium involved in the thermophilic anaerobic oxidation of methane. (6th April 2016) - Krukenberg, Viola; Harding, Katie; Richter, Michael; Glöckner, Frank Oliver; Gruber‐Vodicka, Harald R.; Adam, Birgit; Berg, Jasmine S.; Knittel, Katrin; Tegetmeyer, Halina E.; Boetius, Antje; Wegener, Gunter
Summary: The anaerobic oxidation of methane (AOM) is mediated by consortia of anaerobic methane‐oxidizing archaea (ANME) and their specific partner bacteria. In thermophilic AOM consortia enriched from Guaymas Basin, members of the ANME‐1 clade are associated with bacteria of the HotSeep‐1 cluster, which likely perform direct electron exchange via nanowires. The partner bacterium was enriched with hydrogen as sole electron donor and sulfate as electron acceptor. Based on phylogenetic, genomic and metabolic characteristics we propose to name this chemolithoautotrophic sulfate reducer Candidatus Desulfofervidus auxilii. Ca . D. auxilii grows on hydrogen at temperatures between 50°C and 70°C with an activity optimum at 60°C and doubling time of 4–6 days. Its genome draft encodes for canonical sulfate reduction, periplasmic and soluble hydrogenases and autotrophic carbon fixation via the reductive tricarboxylic acid cycle. The presence of genes for pili formation and cytochromes, and their similarity to genes of Geobacter spp., indicate a potential for syntrophic growth via direct interspecies electron transfer when the organism grows in consortia with ANME. This first ANME‐free enrichment of an AOM partner bacterium and its characterization opens the perspective for a deeper understanding of syntrophy in anaerobic methane oxidation.